Green Financing : One Effort Achieving Sustainable Development - Sulaksana, Fia Dialysa (Banking & Management Review, 2022)
The scope of the economy is to increase revenue and minimize costs, social, namely the welfare of employees, fair trade/business, and participation in charity programs. Green financing encourages the formation of a green industry; stimulates the development of technological innovations through the creation of clean, energy-efficient, and radiation-free environmental technologies; and creates new business growth in the financial industry through the establishment of financial instruments, such as green loans, green bonds, green investments, green funds, and various other financial business opportunities. The purpose of this study is to determine (1) the concept of green financing and sustainable development (2) the dimensions of green financing and (3) the efforts that must be made so that green financing is implemented optimally. The method used is descriptive qualitative. The results of the research are (1) there are 3 (three) concepts of green finance: greening the banking system, greening the bond market, greening institutional investors (2) the dimensions of green financing are achieving industrial, social, and economic excellence; (3) efforts that must be made so that the application of green financing in sustainable development can be further enhanced namely increasing government participation, support and regulation.